Chemical characterization and antimicrobial activity of essential oil and crude extract of lemon grass (Cymbopogon citratus) (Research, Society and Development, 2022)
The search for active ingredients has been increasingly recurrent due to the great interest in new natural antimicrobials, as microorganisms are more resistant to some antibiotics. Therefore, we sought to determine the antimicrobial sensitivity of essential oil and lemongrass extract (Cymbopogon citratus) against strains of bacteria. The essential oil was extracted by hydrodistillation, and the hydroalcoholic extract by the maceration process. The chemical composition of the oil was performed by gas chromatography and the extract by phytochemical tests and quantification of total phenols. In addition, the antimicrobial activity of the essential oil and extract was verified through the disk diffusion technique, and then the minimum bactericidal concentration (MIC) by the tube dilution technique, performing the positive control against commercially used antibiotics. . The majority of essential oil compounds found were Geranyl Acetate, β-Citral and Epoxy-Linalooloxide, while in the extract the most abundant chemical classes were Alkaloids, Tannins, Flavones, Flavonols and Xanthones. The values ​​found in the quantification of phenolic compounds in the extract and oil were 152.82 and 350.95 mg EAT.g-1, respectively. Antimicrobial assays showed that the standard strain Staphylococcus aureus showed the highest inhibition halo (14.00 ±0.765 and 25.33±0.471) and MIC (600±0.00 and 100±0.00) for essential oil and extract, respectively. In strains isolated from food, S. aureus also had the highest inhibition halos and MIC. In view of the results, the chemical composition showed that both the essential oil and the extract showed chemical classes with active biological properties, being possible to affirm that lemongrass is a product with antimicrobial potential.